DEVELOPMENT OF THE DIGITAL ECONOMY IN UZBEKISTAN - Olimova Lola Erkinovna; Melieva Shakhribonu Omonovna (Scholar Express Journals, 2022)
This article talks about the development of the digital economy in Uzbekistan. The development of scientific thought, the introduction of digital technologies and artificial intelligence has led to fundamental changes in economic relations. The formation of the digital economy is a priority direction of the state policy of most economically developed countries, including Uzbekistan
Keywords: Economy; digital program; export; import